Critical acceleration -deceleration allows estimates real metabolic demand during soccer game - Argemi, R.; Ortega, G. P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Since 1950 many different efforts have been made to estimate the metabolic demands of a soccer game, despite the different tools the only published information is about distance and speed during the game. We hypothesize that this approach underestimates the real metabolic demand of a soccer game compared to accelerations and decelerations measure. PURPOSE: To determine the physical demand of a soccer game comparing, running speed vs. acceleration-deceleration. METHODS: We evaluate 10 field players of the profesional team of Boca juniors, Argentina. First, they done endurance intermittent level 2 Yo-Yo Test, with GPS (gpsport®, Australian). We establish the critical velocity (CV) (average velocity of the last step) and critical acceleration-deceleration (CAD). ( aceleration and desaceleration of the last step in 0,5 1, 2 and 3 seconds) Using a commercially available semi-automatic video analysis system we compare the distance covered at different speeds and at different intensities of acceleration-deceleration during an official Argentine first division soccer game. RESULTS: the results for the distance covered in meters; the percentage of the total distance covered; the average distance covered; and the number of efforts are shown for >80%, >100% or >200% of critical velocity (CV) and critical aceleration desaceleration (CAD) Distance in meters (CV: 2271, 1279 and 0) (CAD: 3881*, 2323* and 534*). % total Distance (CV: 22,52, 1274 and 0) (CAD: 38,44*, 23,02* and 5,3*)Average distance per entry (CV: 5.24, 6.49 and 0) (CAD: 2.60*, 3.12*, and 5.3*). * p: < 0,05 . CONCLUSION: Running speed underestimates the real metabolic demands of a soccer game. The average distances of each effort are very short to develop high velocities, even when the players are accelerating at their maximal or near maximal capacity. Considering acceleration and deceleration, the efforts double the values of intense exercise from the traditional methodology which measure only velocity.